2023
DOI: 10.1002/jor.25633
|View full text |Cite
|
Sign up to set email alerts
|

A human meniscus explant model for studying early events in osteoarthritis development by proteomics

Abstract: Degenerative meniscus lesions have been associated with both osteoarthritis etiology and its progression. We, therefore, sought to establish a human meniscus ex vivo model to study the meniscal response to cytokine treatment using a proteomics approach. Lateral menisci were obtained from five knee‐healthy donors. The meniscal body was cut into vertical slices and further divided into an inner (avascular) and outer region. Explants were either left untreated (controls) or stimulated with cytokines. Medium chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…This leads to sectioning artefacts and undesirable variability in the samples being studied. This challenge has also been documented by other researchers in the field [45]. Every possible measure was undertaken to obtain quality sections.…”
Section: Quality Control Step For Histological and Immunohistochemist...mentioning
confidence: 89%
See 3 more Smart Citations
“…This leads to sectioning artefacts and undesirable variability in the samples being studied. This challenge has also been documented by other researchers in the field [45]. Every possible measure was undertaken to obtain quality sections.…”
Section: Quality Control Step For Histological and Immunohistochemist...mentioning
confidence: 89%
“…Regarding meniscal collagen network degradation, it has been theorized that it would occur in areas with significant proteoglycan loss [ 15 ] as aggrecan would shield the collagen network until a sufficient amount of aggrecan was released, allowing MMPs to access the collagen molecules to initiate collagenolysis [ 42 ]. A recent human meniscus degeneration ex vivo explant model found that though cytokine Il-1 induced glycosaminoglycan release, combinations of oncostatin M and TNF alpha induced a much stronger catabolic effect, and the authors propose that these molecules trigger meniscal ECM degradation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations